THE EFFECT OF CITRATE ACID ON THE PRODUCTION PERFORMANCE OF THE QUAIL (Coturnix coturnix japonica) - Ardianto, Roy; Pagala, Muhammad Amrullah; Has, Hamdan (Pascasarjana Universitas Sulawesi Tenggara, 2020)
This study was aimed to determine the effect of citric acid on layer quail (Coturnix coturnix japonica) of production performance. The material used in this study was 80 quail of layer period (12 weeks) observed kept for five weeks. This study was used to complete randomized design with four treatments and five replications. Levels of citric acid administration were 0%, 0,3%, 0,6% and 0,9%, respectively. Parameters observed were feed consumption, egg production, egg weight, and feed conversion. The results showed that citric acid did not have a significant effect (P> 0,05) on feed consumption and quail egg weight, but gave real effect (P<0,05) to quail egg production and gave very significant effect (P<0,01) to feed conversion of quail. The addition of citric acid with a level of 0,6% (P2) gives better egg production and feed conversion than other treatments.Â Keywords: Quail, Citric Acid, Production Performance